Dosage‐dependent effects of monensin on the rumen microbiota of lactating dairy cattle. Issue 7 (18th December 2018) - McGarvey, Jeffery A.; Place, Sara; Palumbo, Jeffrey; Hnasko, Robert; Mitloehner, Frank
Abstract: We examined the dose‐dependent effects of feeding lactating dairy cows a standard diet supplemented with monensin at 175, 368, or 518 mg cow ‐1 day ‐1 on the rumen microbiota. For each dosage, 3 animals were randomly assigned into groups and fed the same basal total mixed ration diet supplemented with monensin, at the respective dose. After 20 days, rumen samples were taken and the effect on the microbiota was examined by 16S rRNA gene sequence analysis and qPCR. At the lowest dose no significant change in 16S rRNA gene sequences associated with any bacterial phyla was observed; however, at the medium and high dosages, we observed significant reductions in sequences associated with gram‐positive bacteria and significant increases in those associated with gram‐negative bacteria that were dosage dependent. All dosages reduced the levels of sequences associated with methanogenic archaea in the rumen, with the medium dosage showing the largest decline. No significant difference was observed for the 18S rRNA gene sequences associated with protozoa in any of the libraries. Our results indicate that with this diet the medium dosage of monensin was most efficacious for the reduction in methanogenic archaea in the rumen of lactating dairy. Abstract : We administered the drug monensin to lactating dairy cattle and examined the changes in the rumen microbiota by 16S rRNA gene sequence analysis and qPCR. We observed statistically significant changes in the levels of gram positive and gram negative bacteria as well as methanogenic archaea.